ANALISIS KOMITMEN ORGANISASIONAL, KEPUASAN KERJA DAN KINERJA PEGAWAI - Zulpikar1 Daniel Budi Santoso2 (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2011)
Organizational commitment, job satisfaction and job performance become central issues for each organizations to achieve their goals. This research tries to analyze and describe those factors in the organization. Descriptive analysis was used asmethode of the research. Data were collected from the employees who were in charge as team leader in the company. Affective commitment, continuace and normative commitment were used as organizational commitment's indicators. Indicators of job satisfaction were used pay, promotion opportunities, supervision, coworkers and the work itself. While indicators for job performance were knowledge of work, quality of work, quantity of work, ability to learn, cooperation-ability to work with others and interest in work. The result shows that three variables (organizational commitment, job satisfaction and job performance) as good or moderate. It could means there are still few indicators need to improve.